Analysis of the Implementation of the Musyarakah Contract in Sharia Financial Practice According to Law No. 21 of 2008 - Risnawati Siregar; Tita Nazwa Natalia; Putri Rizka Anindya; Putra Pamungkas (Jurnal Cendikia ISNU SU, 2025)
The development of the Islamic economy in Indonesia encourages the importance of understanding and implementing musharakah contracts as one of the main financing instruments in the Islamic banking system. This research aims to examine the basic concepts, practical implementation, as well as obstacles and solutions in the implementation of musharakah contracts based on Law No. 21 of 2008 concerning Islamic Banking. The method used in this study is a normative analysis method with a literature study approach and analysis of laws and regulations. The research stages include data collection through document review, analysis of the mechanism for implementing musharakah contracts in Islamic financial institutions, identification of types of musharakah products, and evaluation of obstacles and implementation solutions. The results of the study show that the musharakah contract involves the principle of capital partnership with a fair and transparent profit-sharing system. However, its implementation still faces various challenges such as limited risk management, lack of public literacy, and implementation standards that are not yet uniform. The solutions offered include improving public education, utilizing digital technology, strengthening risk management, and harmonizing regulations. By optimizing the implementation of musyarakah, it is hoped that an inclusive, fair, and Islamic financing system can be realized.